Master’s Degree Program at Osias Colleges, Incorporated… In the Prospect of Educators and Corporate World Employees - Santiago, Lilia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This tracer study examines the Master’s Degree graduates from the Master of Arts in Education (MAEd) and Master in Business Administra-tion (MBA) programs to assess their current profiles, contributions of their respective programs, and their ratings of the degrees earned. Utiliz-ing a survey questionnaire adapted from the University of Santo Tomas, data were collected from both MAEd and MBA graduates through web-based sampling. The descriptive research design was employed to ad-dress the study's questions.The findings reveal that the majority of respondents are females in upgraded positions, such as Teacher III, Head Teacher, Master Teacher, and Principal. Most MBA graduates are employed as Senior High School teachers, with some holding high positions like Corporate Budget Spe-cialist and Senior Financial Planning Specialist. The study highlights that the Master’s Degree Program significantly contributes to the academic profession, particularly in meeting professional needs, enhancing learn-ing efficiency, and fostering people skills and values formation. Gradu-ates rated their professors highly, particularly regarding subject matter knowledge, pedagogical expertise, quality of instruction, and teacher-student relationships. The study recommends that Osias Colleges, Inc. (OCI) Management and Faculty continue to foster a lifelong learning mindset and maintain ongoing communication and networking with alumni to enhance educa-tional outcomes and professional development. This approach will sup-port continuous growth and ensure that graduates are well-prepared for their careers.